An educational advancement in the form of Andragogy based education: A comparison of two different peer assisted learning strategies - Nirmala Anand; Vijaya Dandannavar; Rajesh Shenoy; Jaysheela Bagi (Al Ameen Journal of Medical Sciences)
Background: The transition from Pedagogy to Andragogy in undergraduate Physiotherapy education necessitates addressing educational deficiencies. Objective: To evaluate the educational outcomes of two andragogical teaching approaches: Student-Led Objective Tutorials (SLOT) and Student-Led Socratic Seminars with Concept Mapping followed by Reflective Writing. Materials and Methods: A quasi-experimental cross-over study divided Phase 1BPT students into SLOT and Socratic Seminar groups (n=50). Four physiology modules were covered, and internal assessment scores were compared pre- and post-intervention. Results: SLOT group's mean pre-test marks were 55.4±7.31, with a post-test increase to 61.2±7.42 (6% increase). Socratic Seminar group's pre-test mean was 58.1±6.668, increasing to 67.9±8.19 (9% increase). Around (81%) students found SLOT very interesting, (97%) felt that SLOT improved their deductive thinking, (91%) felt it improved their analytical skills. Around (84%) of students felt that Socratic seminars helped them understand the practical applications of the content and a staggering (95%) of students felt Concept mapping allowed them to organize the flow of processes. The process of reflective writing in these students was highly appreciated. Feedback indicated high student interest and perceived improvement in deductive thinking, analytical skills, practical understanding, and concept organization. Conclusion: Both andragogical methods foster peer learning. SLOT enhances critical thinking, communication, and presentation, while Socratic Seminars promote higher order thinking. Both encourage deep learning through discussion and debate.